Protein misfolding and aggregation of tau protein in alzheimer’s disease - Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Advances in Bioengineering, 2020)
Protein misfolding has interestingly been referred to as the ‘dark side’ of the protein world. The cytotoxicity of misfolded and unfolded polypeptides is due to an overwhelmed quality control system, mainly comprising molecular chaperones to assist in folding, the unfolded protein response (UPR) in the endoplasmic reticulum and the heat shock response (HSR) in the cytosol, which are aimed at clearing misfolded proteins and their early aggregates. When misfolded/unfolded polypeptides exceed the quality control measures of the chaperone–ubiquitin–proteasome clearing system, they form toxic pre-fibrillar aggregates which interact with the cell membrane, disrupting redox potential due to aggregate organization into non-specific membrane pores. In most cases, increases in intracellular free Ca²⁺ and consequent disruption of the redox potential are among the earliest biochemical alterations in exposed cells. An improved understanding of the mechanisms of protein misfolding and intermediate structures that lead from monomers to oligomers ready to aggregate could provide crucial impetus to therapeutic interventions such as upregulating molecular chaperone machinery, use of antibodies and high throughput screening of promising candidate molecules.

Role of microglia in regulating cholesterol and tau pathology in alzheimer's disease - Nanjundaiah, Shwetha; Chidambaram, Hariharakrishnan; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Cholesterol, a principal constituent of the cell membrane, plays a crucial role in the brain by regulating the synaptic transmission, neuronal signaling, as well as neurodegenerative diseases. Defects in the cholesterol trafficking are associated with enhanced generation of hyperphosphorylated Tau and Amyloid-beta protein. Tau, a major microtubule-associated protein in the brain, is the key regulator of the mature neuron. Abnormally hyperphosphorylated Tau hampers the major functions related to microtubule assembly by promoting neurofibrillary tangles of paired helical filaments, twisted ribbons, and straight filaments. The observed pathological changes due to impaired cholesterol and Tau protein accumulation cause Alzheimer's disease. Thus, in order to regulate the pathogenesis of Alzheimer's disease, regulation of cholesterol metabolism, as well as Tau phosphorylation, is essential. The current review provides an overview of (1) cholesterol synthesis in the brain, neurons, astrocytes, and microglia; (2) the mechanism involved in modulating cholesterol concentration between the astrocytes and brain; (3) major mechanisms involved in the hyperphosphorylation of Tau and amyloid-beta protein; and (4) microglial involvement in its regulation. Thus, the answering key questions will provide an in-depth information on microglia involvement in managing the pathogenesis of cholesterol-modulated hyperphosphorylated Tau protein.
Keywords: Alzheimer's disease; Amyloid-beta protein; Cholesterol; microglia; Tau hyperphosphorylation

Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation

Dual modification of tau by pseudophosphorylation and glycation does not enhance amorphous aggregation - Chinnathambi, Subashchandrabose; Sonawane, Shweta Kishor; Chandrashekar, Madhura; Chidambaram, Hariharakrishnan; Thulasiram, Shrivatsa; Kulkarni, Mahesh J. (Cellular Physiology and Biochemistry, 2024)
<h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Background/Aims: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The neurofibrillary tangles consisting of Tau protein are an important pathology in Alzheimer’s disease. The paired helical filaments of Tau form most of the NFTs. These PHFs of Tau are found to carry numerous post-translational modifications, which stabilize them and aid in aggregation. The mechanistic function of Tau is to bind and stabilize the axonal microtubules. Hyperphosphorylation of Tau causes it to compromise its physiological function and accumulate in the neurons in the form of aggregates. Such residue-specific phosphorylation has been studied by employing Tau pseudophosphorylation mutants. But in addition to phosphorylation, several other modifications also aid in stabilizing the Tau PHF. Glycation is one such non-enzymatic PTM caused by sugars and their reactive intermediates. In this study, we employed the pseudophosphorylated Tau double mutants (262/404D, 262/396D, and 231/262) for studying their modification by methyl glyoxal, a reactive intermediate of glucose metabolism.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Methods: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> We studied various biophysical properties like aggregation propensity, Advanced glycation end-product formation, and global conformation of the Tau with dual modifications. Our study includes the use of <i style="box-sizing: border-box; color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">in vitro <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">techniques e.g., ThS fluorescence assay, electron microscopy, CD spectroscopy, SDS-PAGE.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Results: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The overall result of the study suggest that the MG-induced Tau aggregation is influenced by the residue-specific Tau phosphorylation.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Conclusion: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> In conclusion, the combinatorial effect of discreet PTMs on Tau function could lead to a better understanding of Tauopathy.